Pengujian Kualitas Aplikasi Cash Flow Class Berbasis Web Menggunakan Standar ISO/IEC 29119:2022 - Dzulfikar Ali; Tiyas Cahyaning Wulan; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Web-based financial management applications require a standardized testing process to ensure proper system functionality, reliability, and security. This study was conducted to evaluate the quality of the Cash Flow Class application developed using PHP and MySQL, complying with the ISO/IEC 29119:2022 standard. The Black Box Testing method was used in the testing, focusing on functional checks of key features such as login, member management, income, expenses, cash balances, and profile management. Testing was conducted through a series of systematically designed and executed test cases. Based on the test results, the application achieved a 60% success rate, with 18 test cases successful and 12 test cases failed. In addition, 12 bugs of varying severity were found, primarily in modules related to transactions and balance updates. This study provides several improvement suggestions to enhance the quality of the Cash Flow Class application, enabling it to operate more optimally and reliably in supporting web-based cash management.